2005
DOI: 10.1093/humrep/deh671
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality before and after gonadotoxic treatment

Abstract: Gonadotoxic treatment results in a significant reduction in sperm quality. The type of cancer or disease, and the pre-treatment sperm concentrations were found to be the most significant factors governing post-treatment semen quality and recovery of spermatogenesis. All categories of patients displayed varying degrees of azoospermia and oligozoospermia, and recovery of gonadal function from these states was not significant. This highlights the importance of ensuring sperm banking before treatment, including fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 48 publications
2
63
0
5
Order By: Relevance
“…Nevertheless, 30-50% of the patients will not be able to achieve spontaneous pregnancy in the years after the treatment of testicular cancer (9). Before the development of ICSI, the alternatives proposed to patients presenting with spermatogenesis failure were sperm donor or adoption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, 30-50% of the patients will not be able to achieve spontaneous pregnancy in the years after the treatment of testicular cancer (9). Before the development of ICSI, the alternatives proposed to patients presenting with spermatogenesis failure were sperm donor or adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, each patient should be fully informed of the possibility of sperm cryopreservation before the implementation of treatment (6)(7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…94% der behandelten Männer mit Hodenkrebs gute Erholungsraten der Spermatogenese. Bahadur et al [1] untersuchten im Jahr 2005 Spermiogramme von Lymphompatienten, wobei 59% der behandelten Männer eine initiale Azoo spermie aufwiesen. Erst 45 Monate nach Therapieende konnten die quantitativ besten Spermiogramme ausgewertet werden.…”
Section: Auswirkungen Zytotoxischer Therapien Auf Reproduktive Organeunclassified
“…However, there are few reports on sperm production in adults with acute leukemia. Recently, Bahadur et al [5] showed that gonadal toxic treatment for adult patients with leukemia or lymphoma results in significant reduction in sperm quality. Similar results were reported by Lemez and Urbánek [6].…”
mentioning
confidence: 99%